CURRENT TRENDS IN THE REAL ESTATE MARKET IN RUSSIA: PERSONAL CONSUMPTION OF THE POPULATION AND THEIR INVESTMENT ACTIVITIES - Voroshilo, Victoria; Burkaltseva, Diana; Blazhevich, Oleg; Bondar, Aleksandr; Betskov, Aleksandr; Kilyaskhanov, Hizri; Zotova, Snezhana (Revista Inclusiones, 2019)
Real estate market, which covers the personal citizens’ requirements in home ownership, is connected with satisfying their investment activity. This investment activity is aimed at investing funds in commercial and residential real estate, and land plots as well. Herewith, real estate market segments are developing unevenly. The residential and commercial real estate market is actively developing. Land market has average development rates. The purpose of the article is to identify current trends in the real estate market in the Russian Federation. The following tasks have been completed in the framework of the set purpose: systematization of factors affecting the development of the real estate market; analysis of development trends of the residential real estate market; consideration of the land market state.